1993
DOI: 10.3109/00365549309008578
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Response to Varicella-zoster Virus is Inversely Related to Development of High Levels of Varicella-zoster Virus Specific IgG Antibodies

Abstract: We examined specific humoral and cellular immunity from varicella-zoster virus (VZV) in 10 pediatricians, 8 healthy immune adults, 2 non-immune adults, and 15 patients with acute lymphocytic leukemia (ALL) in order to investigate the mechanism of resistance to VZV and the booster effect of frequent re-exposure. The responder cell frequency (RCF) against VZV antigen was determined by lymphoproliferative response with limiting dilution. Four of the 10 children with ALL and receiving maintenance therapy did not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Terada et al (quality: medium, relevance: C) noted that pediatricians had a higher VZV-specific responder cell frequency compared to non-matched healthy adults thereby suggesting a cellular effect of boosting [53]. In a later study, Terada et al (quality: low, relevance: D) also showed that health care workers frequently exposed to VZV had increased serum IgA levels [54].…”
Section: Resultsmentioning
confidence: 99%
“…Terada et al (quality: medium, relevance: C) noted that pediatricians had a higher VZV-specific responder cell frequency compared to non-matched healthy adults thereby suggesting a cellular effect of boosting [53]. In a later study, Terada et al (quality: low, relevance: D) also showed that health care workers frequently exposed to VZV had increased serum IgA levels [54].…”
Section: Resultsmentioning
confidence: 99%
“…zoster. For the analysis of the incidence of zoster, 1 child was not included because her varicella occurred at 5 months of age, which is known to increase the incidence of zoster [7,8]. The child with a low CD4 / cell count and poor growth (who was Discussion judged to have AIDS) when she developed varicella was included in the analysis of zoster but not in the analysis of the We could find no obvious evidence that acute varicella worsened the course of HIV infection in children with regard spectrum of varicella in HIV infection.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in the preantiviral drug era, ú30% of untreated leukemic children develvaricella occurs influences the rate of virus reactivation, as reported for children whose varicella occurred either in utero oped pneumonia or other aspects of disseminated infection. In one study of leukemic children, even after varicella-zoster or during the first year of life [8]. It is possible that as the levels of CD4 / cells in our patients fall with time, the rate of immune globulin prophylaxis, 5 (11%) of 45 developed pneumonia [10].…”
Section: Methodsmentioning
confidence: 99%
“…We note that our antigens consisted of overlapping 15-mer peptide mixes designed to stimulate both CD4 ϩ and CD8 ϩ T-cell responses, particularly when used on thawed PBMC (61). In contrast, many studies in the past, and importantly, the Zostavax vaccine immunogenicity studies, used VZV cell lysate as a stimulus (11,16,38,53,(62)(63)(64)(65). Thus, any change in the CD8 ϩ component against VZV might have been missed.…”
Section: Fig 3 Comparing Ifn-␥-producing T-cell Percentages (Of Cd3mentioning
confidence: 99%